(untitled) - HENDRA WICAKSONO, IGN (Language Horizon: Journal of Language Studies, 2014)
Motherhood in Toni Morrison’s Beloved Ign. Hendra Wicaksono English Literature Faculty of Language and Arts State University of Surabaya don.ignasius@gmail.com Hujuala Rika Ayu, S.S., M.A. English Department Faculty of Language and Arts State University of Surabaya ayuhujualarika@yahoo.com Abstrak Studi dalam Novel Beloved oleh Toni Morrison ini berpusat pada Ibu. Analisis dari sosok ibu sangatlah penting dan layak untuk didiskusikan karena ini adalah fenomena yang terjadi hampir di masyarakat. Perempuan yang mempunyai naluri keibuan cenderung untuk sayang pada anaknya; melindunginya, mencintainya dan mengasuhnya, namun beberapa ibu kadang-kadang memiliki cara ekstrim seperti Sethe yang membunuh anaknya sendiri. Ini merupakan bagian dari karakter utama Sethe di novel Beloved. Berdasarkan fakta diatas, masalah yang ditimbulkan terbagi menjadi dua pertanyaan (1) Bagaimana sifat keibuan dari seorang ibu berras hitam yang digambarkan dalam novel Beloved oleh Toni Morrison? Dan (2) Apakah pengaruh perbudakan dari sosok keibuan Sethe dalam novel Beloved oleh Toni Morrison? Data dalam thesis ini berdasarkan novel Beloved sebagai sumber utamanya. Data yang dimati dalam bentuk bagaimana ibu ini sebagai objek yang tertindas, bagaimana pula penggambaran dari ibu ini, dan bagaimana juga pengaruh perbudakan yang dialami ibu ini dalam hidupnya. Yang digunakan dalam hal ini adalah bagaimana sejarah hubungan antara ibu dan anak ini dalam novel. Menunjukkan bahwa adanya penggambaran sosok seorang ibu pada Sethe. Dia adalah figur utama dalam novel ini. Alasan yang kedua adalah pengaruh perbudakan ini terhadap Sethe. Dia mengalami perasaan trauma yang berasal dari latar belakang hidupnya. Kata Kunci: Keibuan, Beloved, Sethe dan Perbudakan Abstract This study is centered on the analysis of motherhood in Toni Morrison’s Beloved. This analysis of motherhood is very important and worthy to be discussed because it is a phenomenon which happens almost in society. Woman as a mother has “a maternal instinct” caring her children; protecting, loving and nurturing, but some mother sometimes do an extreme action, such as Sethe murdering her own child. This is the case of Beloved’s main character. Based on the fact, problems arise along with to two main questions of (1) How is motherhood in Black mother depicted in Toni Morrison, Beloved? and (2) What are the influence of slavery to Sethe’s motherhood in Toni Morrison, Beloved? The data of thesis are gathered from the novel as the main source. The data observed are in the form of how the motherhood of a slave mother as the oppressed object, how motherhood in black mother are depicted, and also how slavery influence motherhood. The used the history of motherhood to talks how about relation between mother and her daughter in this novel. The show finds the depiction of motherhood in Sethe. She is the central figure of the novel. The second reason is the influence of slavery to Sethe’s motherhood. Sethe is traumatic experiences become her traumatic backgrounds. Keywords: Motherhood, Beloved, Sethe and Slavery Introduction As a part of American people, Afro-American is still a marginalized group in gaining education as well as important position since they are considered as lower class by the whites. The marginalization of African American people in America started when they were first brought to America as indentured servants and then slaves. In relation with their status as slaves, the marginalization also shows that slavery has not ended, yet it remains in the other forms. Furthermore, the separation of whites from blacks in America has never changed significantly. Consequently, the status of ‘black’ in America remains the same, as the second class in America. All these facts awake wonder to know the life of blacks further. To satisfy the wonder, chooses the work of an African American writer in order to understand their life. One of the Afro American greatest writers is Toni Morrison. Toni Morrison was born Chloe Anthony Wofford in Lorain, Ohio. Morrison began her writing career in 1957 when she returned to Howard as a lecture. Although she is considered as a twentieth century writer, her stories are about the past. She is married to Harold Morrison, a Jamaican architect.During the marriage Morrison joined a writer’s group at Howard, she writes her first novels, The Bluest Eye (1970), Sula (1973), Song of Solomon (1977), and Tar Baby (1981). Morrison’s novels are characterized by meticulously crafted prose, using ordinary words to produce shiny, lyrical phrases and portray precise emotional perception (Tate, 1984: 117). Toni Morrison focuses on the black female and this theme gathers strength in her later work, where she considers the issues of female friendship, different aspect of love and mother-daughter relationship. Morrison always emphasizes her works on the past life of the Blacks and distinguishes herself from other modern writers (Tate, 1984: 426-427). Being a black writer, she tries to portray the past life of black’s especially about slavery and combined it with her make up stories. Her make up stories are from her own black folks and community in which she grew up (Wilentz, 1992: 81). Morrison invites the readers to ask question important history and she is trying to say that not all of the truths are being recorded in history. Morrison’s is the third black American, and the second black America woman receives the Pulitzer Prize for fiction, in 1988 for the best-selling Beloved (1987). This novel also made into movie in 1993. Toni Morrison is put on the portrayal of her characters especially her female characters. The portrayal of these female characters is always connected with the hardship of life in the time of slavery. Morrison focuses the story on the marginal group at the time in order to make the people realize that the human beings feelings and emotions toward their surrounding environment (Tate, 1984: 121). According to Tate, Another critics said of her that the characters in Morrison novels are the representatives of sustaining values of life in past time that appear within the black community (Tate, 1984: 815). Morrison is also regarded as a black woman writer who tells life of black in the past time so vividly. For all of these, the writer chooses Toni Morrison as well asto discussed in this thesis. The novel is based on true story of the slave Margaret Garner, who murdered her own child rather than returns her to slavery. The novel takes place in 1873 Cincinnati, Ohio. After escaping from Kentucky plantation the main character, Sethe, attempts to kill her children to prevent them from being enslaved. She succeeds in killing only one of her four children the crawling already girl. This event, in all its brutality, condemns Sethe to be rejected by society. She then seeks refuge within the walls of her house at 124 Bluestone Road, where she separates herself as well as her daughter, Denver, from the black community. Sethe murdered her young daughter to prevent her from slavery. The baby’s ghost plays a much more destructive role in the house 124. The baby’s ghost shows-up as the 19-year-old “Beloved”, Beloved appears as a young woman, but behaves like a child. Consequently, she comes back to claim what was taken from her. Beloved is full all of history and memory, especially talking about history and memory in slavery times. Morrison always emphasizes her works on the past life of Blacks and distinguishes herself from other modern writers (Goldstein, 1989: 49). Being a black writer, she tries to portray the past life of black’s especially about slavery and combined it with her make up stories. Her make up stories are from her own black folks and community in which she grew up. Morrison concerns with the social condition in the slavery times and the African American Community, she additionally focuses on the inner psychic that has been destructed by her knowledge of slavery. Moreover, her emphasis in one of her novel, Beloved reflects the effects of slavery to the African American people. White racial oppression aimed at devaluating and abusing all black people without exception, and that actions tend to bring black women into suffering. African American and Native American cultures is manifested in the form of hybridity, in the theme of motherhood it reveals itself in the form of subversion The family had to depend more on family members and roles which were preserved partially due to the enforced segregation, isolation, and insularity of Black families” (Joseph 89). Thus, she contends that “the Black family in concert developed and established new roles, combining the requisites of the new society with all that could be maintained from the old” (Joseph, 1981: 90). The signs of this Afrocentric ideology of motherhood she uncovers, for example, in traditions surrounding the Mother’s Day celebration. Despite the fact that the holiday is a nationwide phenomenon and is not limited to black families, “the style and manner of celebration for Blacks has cultural differences and the role of honor and respect for the Black mother has its roots in African history” (Joseph, 1981: 87). Patricia Hill Collins in her article The Meaning of Motherhood in Black Culture and Black Mother/Daughter Relationships identifies major conditions that are implicit in white perspectives on motherhood, forming the foundation for the cult of true womanhood, but are particularly problematic for African American and Native American women, as well as other women of color. According to Collins, The idea of the cult of true womanhood has been held up to Black women for emulation, racial oppression deprived black families of sufficient resources to support private, nuclear family households. Moreover, due to the same reason, black women were unable to conform to the white middle class standard of strict sex-role segregation, according to which to be considered a ‘good’ mother, one was supposed to stay at home, making motherhood a full-time ‘occupation’ (Collins, 1991: 327), while developing a complete economic dependency on men. Both of those conditions are equally uncharacteristic for African American and Native American families. The difference is especially laid on the preparation to have a family. A black mother is prepared to have a single parent house hold while white woman does not have that. Because of that opposition, Morrison describes clearly the influences of depression of being a black woman slave as well as a black mother. Toni Morrison as an author makes this study quite challenging because of her concern, as a black female author, on historical, fact, and memory during slavery times. The slavery system not only consumed the black physically but also destroyed them spiritually. In Beloved, Sethe a black woman and mother, is suffering from loss of motherhood under slavery. Motherhood posed a problematic challenge to Afro-American women under the slave regime. This situation does not allow for free mother in caring for the children or perform their biological role as caregivers and mothers to their children, and especially their female children, had very debilitating consequence on the psyche of the women. At last, the writer hopes this thesis becomes stepping stone for the readers to analyze Toni Morrison’s Beloved more deeply and also expects the readers to have a picture of motherhood. RESEARCH METHOD This study takes the data source of this thesis is a novel entitled Beloved written by Toni Morrison. It is first published by Penguin Group (New York) in United States of America in 1988. This thesis will analyze dialogues between characters, their opinion and actions based on Toni Morrison’s Beloved. Dialogues, actions, and statements which are concerned motherhood will be used as the quotation revealing both first statement and second statement. While to motherhood of the first statement of the problem refers to the present time, to reveal the contributing factor of the mother’s relations style it will deal with the image of the mother’s past. In addition, dialogues, opinions, and actions related to daughter’s character development will be used to reveal the third problem. Each part of the data is the evidence and justification during analyzing process. The impact of the motherhood concept on the daughter’s character development in Toni Morrison’s Beloved approaches by two main concepts. First, the concept is motherhood. In this case, the concept will be used to motherhood it reveals itself in the form of subversion. The second concept is Slavery. In this case, the concept their status as slaves. The last concept is Race. Race is a classification systems used to categorize humans into large and distinct populations or groups by anatomical, cultural, ethnic, genetic, geographical, historical, linguistics, religious, or social affiliation. First step of making an analyzing is close reading. Reading novel is important to accomplish the themes of the novel. After being agreed that this novel is suitable for the thesis by the thesis supervisor, the title of the thesis is easily found. The next procedure is making an outline of the whole content of the thesis. In the outline of the thesis it has been decided what the statements of the problem is going to be. The problem above is also under the supervision of the thesis supervision. Two statements of the problems appear in this thesis entitled “Motherhood in Toni Morrison’s Beloved” They are how is motherhood in Black mother depicted; the causes of Sethe’s motherhood; and the impacts of Sethe’s motherhood The analysis process starts by doing closed reading on Toni Morrison’s Beloved as the source of the data. The first closed reading is to find the quotations which are taken also related to the violence that the owners do to the main character. Before conducting this study, there are some steps to do. First is reading the novel and find the theme which is found in the novel, then the second step is close reading which is useful to find and quotes the quotations that indicate the theme that supposed to be discussed. The quotations here refer to any kinds of statement or sentences that show motherhood and the main characters show the mother’s feels with the child. MOTHERHOOD Motherhood refers to the relationship of the mother to her child as a sociologic, physiologic, and emotional whole (Deutsch, Helene 1973: 20). The words for mother and mud (earth, slime, the matter of which the planet is composed, the dust or clay of which ‘man’ is built) are extremely close are many languages: mutter, Madre, material, moeder, modder. The name Mother Earth still has currency, although, significantly, in our time, it has acquired a quaint, archaic, sentimental ring. Motherhood is a communal affiliation. In biological motherhood, as in these other activities woman was not merely a producer and stabilizer of life: there, too, she was a transformer. Menstrual blood was believed to be transformed into the and into to milk which flowed from the mother’s breasts. This relationship begins with the conception of the child and extends through the further physiologic processes of pregnancy, birth, feeding and care. All these functions are accompanied by emotional reactions that are to some extent typical of or common to the species but for the most part vary individually, for they are inseparably connected, in each woman, with the total personality. Woman did not simply give birth. She made it possible for the child to go on living. Her breasts furnished the first food, but her concern for the child led her beyond that one-to-one relationship. The woman’s body, with its potential for gestating, bringing forth and nourishing new life, has been through the ages a field of contradictions: a space invested with power, and an acute vulnerability; a numinous figure and the incarnation of evil; a hoard of ambivalences, most of which have worked to disqualify women from the collective act of defining culture. The mother’s love for the child is often associated with the fact that she considers herself absolutely and exclusively indispensable to him. Woman’s love for her child is normally greater than her self-love, and the idea of eternity inherent in reproduction overcomes her fear of being destroyed. The contemporary woman experiences as uncleanness, pre patriarchal women may well have understood as one of their sacred mysteries. In primitive communities a woman’s whole life is focused around the regular changes of her physiological cycle. Periods of work at home and in the community of social life with her neighbors and of marital relationship with her husband, alternate with periods of seclusion. At regular intervals she is obliged to go away alone; she may not cook, nor tend the cultivated patch, nor walk abroad; she is precluded from performing any of her customary tasks; she is compelled to be alone, to go down into her, to introvert. Anthropologist, who, as a rule, are more interested in the customs of a tribe than in the psychology of individuals, have not asked what effects these customs have on the women themselves. Yet, this periodic seclusion must inevitability have had a profound effect on the woman’s relation to life. (Harding, 1970:70) The stereotypical view that motherhood comes naturally to women may have no basis in fact, but it does have an influence on women’s feelings and attitudes. Almost all women in every culture accept being a mother as a source of immense pleasure and pride (Oxford, 1983:281). Because it is difficult to carry “a mother” status, how they bear and nurture the children, breast-feeding and raising them, doing the household chores, even men cannot doing it well, makes women so proud to call their self “mother”. In some cultures, even a woman was seen as being closer to God than a man, for she alone had been given the power (Gray, 1996: 26). They were honored because of the gift and capability to bearing children. Women felt proud of their biological roles, since mothering was highly respected, and even considered sacred. The parenting process itself totally put and identified mother as “the visible God”. Parenting is the process of promoting and supporting the physical, emotional, social and intellectual development of a child rather than the biological relationship. Mothers were assumed to love their children infinitely and unreservedly, to be glad to devote their self completely in their role, and to want to be with their children at all times. (Oxford, 1983: 285). Jaggar in Tong stated that a person does not need to be a biological mother in order to be a social mother (1998:80). A bonding between mother and another children, not their own, or the bonding among women themselves, could be the media and impact to reveal the motherhood feeling. Naturally, women had instinct to keep and nurture each other, no matter to their peers or other younger person. Oakley in Tong (1998) also explained that social mothers are just as effective as biological mother (81), while Firestone added that people do not need to be biological parents in order to lead child–centered lives (82). Oakley claimed that studies have shown, adopted children are at least as well adjusted as non-adopted children. Though these theories, known that there must be not bearing a child at first to feel and applied motherhood in women’s self. Their instinct appears as natural as they accepted the bonding and womanhood to each other. Mother is perceived not only just as a woman who bore a child but also as a carrier of a tradition “whose continuance signals part of cyclical way of life” (Reynolds 2007: 179-180). In her article “Mother Times Two: A Double Take on a Gynicentric Justice Song” Margot R. Reynolds Argues that The term ‘mother’ or ‘grandmother’ in many Native American tribes signifies woman who is committed to wholeness and well-being. This kind of committed to wholeness and well-being. This kind of commitment can manifest itself in multiple ways – from gardening to childbearing to mentoring (177) Moreover, as Reynolds accentuates, the continuance of tradition has an especially strong and essential role in mother and daughter relationship. According to Paula Gunn Allen that your mother’s identity is the key to your own identity naming your mother (or her equivalent) enables people to place you precisely within the universal web of your life, in each of its dimensions: cultural, spiritual, personal, and historical. Failure to know your mother is failure to remember your significance, your reality, your right relationship to earth and society. It is the same as being lost-isolated, abandoned, self-estranged, and alienated from your own life. (Allen 1986: 210) RELATION BETWEEN MOTHER AND DAUGHTER The relation of a mother and her child, especially daughter is considered simple that every woman takes it for granted. It seems that the problems that existed between them are also regarded as the simple ones. In fact, this relationship is not so simple since it involves two closely related persons who have different perspectives. Woman has wide opportunities for making compromise between motherhood and her other, more personal needs, drives and interest. Many variations in the psychology of motherhood as there are mothers. The capacity for these compromises is based chiefly, apart from reference to the cultural opportunities, upon the fact that woman’s motherliness and femininity are not the only wellsprings of her psychic forces. Being a mother is a hard thing to do. A mother-daughter relationship is one of the most intricate relationships to live. A woman once said to Harding (1975), a psychologist: If you are a bad mother your child naturally reproaches you and lays all the blame for his difficulties in your child inexpert treatment of him. But if you are a good mother you will still not escape blame and reproach. For now it is said that by your very kindness and skillful handling you have bound him to you in an inescapable fixation (158) It is agreeable that the above quotation shows how difficult it is to be a mother. Whenever a problem concerning to a child occurs, the mother is the first and in many cases the only to the blame. Fortunately, Harding explains that it is not the way it should be. The relationship between mother and child is so deep and so fundamental that should surely begin with an a priory belief that their interest cannot be inherently opposed. Whenever a problem occurs, any real solution must take into full account both child and mother. A problem, which usually happens between a mother and an adult child, is that the bond between them, which was at first based on an instinctive mutual love, is replaced by a struggle for dominance. If the mother has no intention to dominate, the child then will have to fight his own childishness but not the mother’s autocracy. This is a growing relationship, which often holds mutual affection. As the years go on and the importance of the age gap lessens, they will be on the more equal basis, and the relationship will become an increasingly satisfying one. On the other hand, if the mother remains unconscious of the possessive trends which are hidden in her love, there as a necessary consequence comes a time of conflict between mother and children. As the boys and girls grow to be a young men and women, reach out naturally for greater liberty and for release from the ties, which bind them not only to their parents but also to their own child. Another mother thought that her love for her daughter was all-sufficient and that the latter’s love marriage and happy motherhood were an unnatural crime. The mother must now teach her child to control his instincts and the better her own instinctual life is controlled, the better does she succeed in this task. She must not be too mild in her methods of training, for excessive indulgence involves the danger of the child’s remaining undisciplined and dominated by the mother instincts. The mother as receiving station for the child’s affective impulses, and that mother and child gradually develop each a gift for observation that is based upon a deep community between mother and child. The mother’s identification with the child may also assume distorted forms. For instance, egoistic self-love does not allow some mother any identification expect that of the child with their own ego. The mother’s fear of separation from the little daughter who moves away from her expresses itself in the same way as her fear with regard to the son only while the children are little. The mother’s fear of losing her daughter, added to the daughter’s overcompensated hatred, results in an excessively strong tie between them. The mother feels abandoned, and as a result of her fear of losing her daughter, together with her fear of the consequences of her daughter’s independences, she intensifies her wooing or attempts to exert an authoritarian power over her. The mother tries to keep him attached to her and opposes the actions that tend to dissolve the tie. The mother’s striving to have her child identify with herself. Usually experiences of the mother’s own childhood are involved here. A mother, who lives in the constant and anxious awareness that she will have to give up her children development, behaves controlling herself more or less like someone who must give up an important, valuable, indispensable part of his own personality together with his beloved object. A mother also feels the psychic umbilical cord with particular intensity. She bears separation from her child very badly, she must be informed of his condition at every moment of his life, and her happiness and wretchedness depend completely upon him. A mother asked for help from a social agency because she was no longer in a position to maintain her home and support her children. A mother must not strive to achieve any other goals through her child but those of his existence; otherwise she runs the risk of failing in her purpose and of being cheated of the experience of motherhood. Another mother presented a similar case. She told her pampered, talented little daughter, to whom she knew that she would give the best possible upbringing and education, that she would eventually be apprenticed to a poor little shoemaker and would suffer many privations in his house. The woman who says of her grown sons and daughters, they will always be children to her, it’s fails to identify them as separate individuals apart from her. If she is so to release her from this problem, she must be willing to give up her part, which rests simply on the fact that her child will become a grown up person when he/she was still unconscious infants, instead of relating her child will still be a child even if he/she is growing up. In discussing some past action of hers which her son and daughter are questioning, she must not take her stand and say, “I am your mother and therefore I know best. Say no more about it.” She must say instead: I did thus and so according to my best judgment then. I had to decide for myself and also for you because you were too young to be able to judge. I may have been wrong; if so, I am willing to change my attitude (Harding, 1975: 186) Saying this she declares strongly her real superiority-the age and experience greater than theirs at the time but she does not shelter herself behind the all wisdom of a mother. This leaves for the youth a place on which to stand. He gains the idea of why the decisions are made, of how judgment can change. As he grows older, he can begin to estimate the reason of his mother’s decisions, and as he learns to make a responsible judgment the mother can disentangle herself from the necessity of thinking for him. The dependence of a child upon a mother is reality. And the positions of the dependence involves, inevitably, the giving in to the authority of the one depended on. That authority can be used wrongly or rightly. It is abused if, by virtue of the power it bestows, the parent assumes some mysterious and permanent superiority. The attitude which says, I want to make you happy, to make life easy for you. I want to guard you from every breath of hardship and adversity, it is terrible. It seems so kind, yet it is really so cruel. It is nothing less than an attempt to play God to the child himself/herself. It is rightly used if it is carried as a responsibility until the child is able to stand on his own feet. Mothers and daughters have always exchanged with each other beyond the verbally transmitted lore of female survival a knowledge that is subliminal, subversive, and preverbal. The knowledge flowing between two a like bodies, one of which has spent nine months inside the other. The experience of giving birth stirs deep reverberations of her mother in a daughter; women often dream of their mothers during pregnancy and labor. A mother was once also a daughter. As a result, many women spend their time to fight against becoming like their mother or unwittingly repeating their mother’s lives (Debold, 1994: xviii). Many women want something different from their daughter no matter how good their relationship with their own mother is (Debold, 1994:5). Mothers have hope for a different world and a different relationship for daughter, so did their mothers before them. Their hope for their daughter is for a future with less stress and with more joy. Therefore, becoming a mother of a daughter is one of the most powerful and most roles (Debold, 1994:7). Most women carry the great responsibility for mothering alone (Debold, 1994: xviii). Therefore, a daughter’s physical safety is the first concern of mothers. For mothers to be able to succeed, they first must be safe from harassment, violence and abuse (Debold xix). Most importantly, the violence will stop when women support each other. Tracing the role of mothers, it can be concluded that becoming a mother is hard. Mothers are the ones who are blamed for the pain that their children experience (Debold, 1994:25). Women who become mothers are asked to take the blame for her daughter’s behavior. If a mother is a bad one, giving the children no special consideration, she may still be the one to blame. While she is a good mother, devoting herself to her children’s needs when they are young, still she is the one who takes the blame when the children cannot be independent as they grow older. Much of the recent discussion of “Family Values” is actually referred to mother blaming: Families are in the trouble not because of the inequities in our economic, child care, and health care systems but because mothers are not doing their jobs right (Debold, 1994:27). The culture of mother blaming creates a psychological prison for mothers of daughters. Whether or not a mother is conscious of this power within the culture, the desire to do right, to provide a daughter with new opportunities make mothering incredibly pressured. Then, a good mother is a mother who is all-nurturing, all-loving, and selfless (32). Love is defined as compete self-giving, taking no thought of its own interest but seeking for the good of the other. Most mothers love their children, want the best for them, and feel enormously guilty when they are told that they are not meeting their children’s needs (34). However, in the slave culture their love is given more to their daughter because the daughter is the one who has close relationship with her mother. In order to be a good mother for her daughter, a mother has to meet the standard of perfection and self-sacrifice: I can protect my daughter from the harsh realities of the world if I do not talk about such things or if I say everything will be okay or if I say just right things (Debold, 1994:35). Of course, there are some kinds of satisfaction which are achieved through the daughters not mothers themselves. Debold said of the satisfaction in her book Mother Daughter Revolution “My daughter can have whatever I did not have” (Debold, 1994:35). In the absence of a father in the home, mothers in a single parent household play the role as the true head of the household. Mothers of single parent household have more authority to control over their daughter’s lives than mothers may have experience of holding household. This feature is found within many African-American communities in which women share the responsibilities of mothering within their communities. The complex interaction of West African traditions with the intentional destruction of families under slavery gives many African-American women a very different sense of responsibility for children than middle class women have. Black women’s feeling of responsibility for nurturing the children in their own family have stimulated a more generalized ethics of care where black women feel accountable to take care of all black children Concerning the theory of African-American motherhood, Reddy identifies “the black female body as the site of a series of visible marking and naming or re-naming. Still, according to Reddy, marking is “the product of abuse and linked to societal inscriptions on the body of the other” (Reddy, 1991:46). This marking also has connection with the enslaved African-American woman with child whose body can flee slavery but it cannot flee from the needs of her children (Reddy, 1991:47). Furthermore, three important things are connected with African-American motherhood that is milk, breast, and blood. Since the children are the own blood of mother, breast feeding is one expression of responsibility for raising the children. For a mother, fulfilling her children’s needs is one of her duties but a slave mother always cannot do that because the slave mother doesn’t many times to fulfilling her children. As a result, maternal functions depend on the biological need for the milk which is produced is one’s own body for one owns children as a value of motherhood. Milk as the only valuable thing that a slave mother can give to her children is also stolen by others. Oftentimes, slave mothers are forced to breastfeed their master’s babies depriving their own children of their rightful breast milk. Because of that, a slave mother feels that she cannot give deep love to her children. Moreover, she has to deny her responsibility as a mother concerning biological need for her children. SLAVERY One of the most important events underlying a conceptual understanding of racial oppression in the US is that of slavery. Slavery of African-Americans led to greater freedom for poor whites, though maintaining an economic structure that would continue to keep the latter poor. Therefore, from the very start of race-relations history in the US, white society has needed African-Americans in terms of performing undesirable employment for the benefit of whites. Slavery was such a engrained element in early American society that it was codified in law by the 1750s and even some of the earliest presidents such as Washington and Jefferson owned slaves themselves. From as early as this time, and onwards, African-Americans have always been fighting for freedom as a collective, while ‘whiteness’ was perceived in this context as some sort of exclusive, individual property (Marable 2002: 3). According to James Oliver Horton and Lois E. Horton in their book, Slavery and the making of America, “slavery was a coercive system sustained by the mobilization of the entire society, and its maintenance rested on the use of unimaginable violence and the constant threat of violence.” (James Oliver Horton and Lois E. Horton, 2005:11) Most Africans people understood slavery, since slavery was an ancient institution that had been established in North and West Africa before European involvement in the trade. In West Africa, land was not held as private property, and slavery, the ownership of other human beings and their labor, was a major basis of wealth. Slaves thus had measurable value, and trading in slaves was a part of commerce. (James Oliver Horton and Lois E. Horton, 2005:20) In the United States, slavery is an old story from the past. Almost all of its states have slavery issue. The common slave back then was a black. White colonists tended to buy black slaves because of their strength, although the reason about white superior which soon led to racism was a different story. Dorothy Schneider and Carl J. Schneider wrote in their book, Slavery in America (American Experience) that as the early slaveholders became experienced, they began to look for slaves from particular African tribes. Koromantees, including the Fanti and the Ashanti, were said to be “remarkable for their extraordinary strength and symmetry, their distinguished appearance and proud bearing. They were blacker and taller and handsomer than their fellow slaves; vigorous, muscular and agile intelligent, fierce, ruthless in war, fanatically attached to the idea of liberty, and strangers to fear.” (Dorothy Schneider and Carl J. Schneider, 2007:50) Owning slaves was legal in the United States. Slaves helped their master in plantation jobs mostly. Although the white colonialist could hire people to help them taking care of their plantation, they tended to have slaves because slave ownership conferred not only wealth but also prestige and status. Even the two-thirds or so of white southerners who did not own slaves had a stake in the slave system, for it supported the myth of white superiority (Dorothy Schneider and Carl J. Schneider, 2007:53) Being slaves did not always mean a lifetime loyalty to the master. Slaves could buy their freedom too. A slave would promise to support himself and pay his owner a profit out of the wages he earned by running his own business or working for another employer. Other slaves managed to save enough to buy their own freedom. It sounded good chance for the slaves, but buying oneself was always a risky business, because owners often failed to keep their promises of freeing the slaves (Dorothy Schneider and Carl J. Schneider, 2007:60) After the slaves were free, it would not be the happy ending. After all, free blacks faced a hostile environment, filled with racial prejudice. Even in free states they were shut out of many occupations and their civil rights were rigorously limited (Dorothy Schneider and Carl J. Schneider, 2007:61). Although black slaves were free, they faced another difficulty. Being kidnapped and sold (again) into slavery was a real and present danger for free backs in both free and slave states (Dorothy Schneider and Carl J. Schneider, 2007:59) The history of slavery is central to the history of the United States, and so this is also a story about the values and events that shaped American society. White Americans committed to freedom and God-given rights found it necessary to justify their economic system based on slavery from the country and the world. Others rationalized the contradiction with theories of racial inferiority, arguing that black people were particularly well-suited for enslavement, that they benefited from enslavement or that slavery was necessary for their control. Although slavery was abolished nearly a century and a half ago, the racism rooted in the nations attempts to justify it remains with us today as the legacy of American slavery. (James Oliver Horton and Lois E. Horton, 2005:11) RACE Race as a constructed social category derives its power partially not only from the social psychological dynamics of social-categorization per se, but also from the powerful taken-for-granted legitimacy which race categories have acquired in their historical formulation. Race is one of the most misunderstood, misused, and often dangerous concepts of the modern words. It is not applied dispassionately by laypeople or even, to a great extent, by social scientists. Rather, it arouses emotions such as hate, fear, anger, loyalty, pride, and prejudice. It has also been used to justify some of the most appalling injustices and mistreatments of humans by other humans. The power of “race” as a way of comprehending human diversity lies essentially in our case with categorization. The idea of race is primeval. Humans have given names to their varied strains since physical difference first began to appear. It has a long history extending as far back as ancient civilizations. It is in the modern world, specifically, the last to two centuries that the notion has taken on real significance and fundamentally affected human relations. In people usage, it has been describe a wide of variety of human categories, including people of a particular skin color (the Caucasian “race”), religion (the Jewish “race”), nationality (the British “race”), and even the entire human species (the human “race”). Race continues to preoccupy the public mind, a reminder of a past that cannot be willed away. Race is a population of human classified on the basis of certain hereditary characteristics that differentiate them from other human groups. Races are, in a sense, pigeonholes for categorizing human physical types. Efforts at classification, however, have created a virtually hopeless disagreement among social and biological scientist. People attach significance to the concept of race consider it real and important division of humanity. And, as long as people believe that differences in selected physical traits are meaningful, they will act on those beliefs, thereby affecting their interrelations with other. If men define situations as real they are real in their consequences (Thomas and Znaniecki, 1918: 79). As should now be obvious, the term of race is so charged and misconceived that it is very difficult to employ in a useful analytic manner. Adding to the confusion is the fact that many groups now defined as ethnic groups were in previous historical periods defined as races. Immigrant groups in the United States, for example, representing different nationalities or religions (Slavs, Italians, Jews, and so on) were classified as races during the early part of the twentieth century by laypersons and many social scientists as well. Race-based policies, for all their pseudo liberal appearance, are in fact conservative, if not downright retrogressive, because they detract from a sound structural analysis of relations of power and relations of production that account for the different positions of various class, racial, and ethnic groups in American society. Relations between blacks and whites are common the personal option of ignoring race. For whites it is paternalistic and ultimately based on the unstated premise that Blacks are categorically inferior and therefore in need of special treatment. For Blacks, it invites the game of manipulating white guilt with the threat of moral blackmail in order to obtain differential (not equal) treatment. Black Americans spend much of their lives at a distance from white Americans, in part because they feel more comfortable that way, and partly because their separation has been imposed by white America. As will be seen later, this helps to explain why even better off blacks tend to do less well than whites on test used by school and employers. Since black of all classes are more likely to be raised in segregated surroundings, they grow up with less exposure to the kinds of reasoning that standardized examination except. From slavery through the present, the nation has never opened its doors sufficiently to give black Americans a chance to become full citizens. Many black men and women are conducing that they can best be described as Africans-Americans, considering how much their character and culture owe to their continent of origin. A pride in this heritage and history has helped them survive slavery and subsequent discrimination. Indeed, the nation as a whole has benefited from black Americans who bring to life the rhetoric and rhythms of their ancestral origins. Racism is the belief that a particular race is superior to inferior to another, that a person’s social and moral traits are predetermined by his or her inborn biological characteristics. Racial separatism is the belief, most of the time based on racism, that different races should remain segregated and apart from one another. Racism has existed throughout human history. It may be defined as the hatred of one person by another or the belief that another person is less than human because of skin color, language, customs, place of birth or any factor that supposedly reveals the basic nature of that person. It has influenced wars, slavery, the formation of nations, and legal codes. Standfield said that coming to Stanford in 1950, it did not take me long to realize that the United States too was a profoundly racist society and exhibited a form of racism that struck me as peculiarly ridiculous: these ignorant, provincial colonist of a barely conquered frontier who could not even place on map were looking down at their race ethnic, economic, and social classes. It shows that United States is formed by many races to be unity. Standfield also said in his theory that feminist standpoint theorist draw from Marxist theory the idea that maternal life structures and sets limits on the understanding of social relations; thus the vision of the ruling class, race, and gender is partial, because it not only structures the material relations in which all are forced to participate, but also takes for granted the labor, indeed the very existence, of oppressed group (H. Standfield, 1993: 42). From this statement said that Marxist theory also classifies the materialism as a concept to separate the race, gender, and class social. So, there are many groups of social life. This statement can say that there is the relationship between materialism and racism. E Franklin Frazier describes the behavior of middle-class African American is strong enough. And it is also socialized as inferior. It means that there is a low social class in America; a black community is as middle-class in America. THE DEPICTION OF MOTHERHOOD IN SETHE Morrison’s Beloved centers the story on Sethe, she is the central figure of the novel and protagonist character. According to Potter there are several ways to identify the characterization of the main character by looking her physical appearance, family background, social background, mental quality (Potter, 1967: 6). To support the analysis in that novel, he also justifies Sethe’s characterization by how the character sees her, and how the other characters see her. Sethe is a woman slave and her skin is dark complexion and has ability to deliver a baby is poured in ”…..Sethe the only female slave, pregnant every year …“ (Beloved, 9). At the quotation shows that Sethe has a woman slave and her skin is black and has ability to deliver a baby. From this quotation shows that Sethe was pregnant she decided to run off from the plantation. Sethe’s has unique physical appearance different with other people. This quotation has reflected that Sethe physical appearances... – The one with iron eyes and backbone to match …. Her face was eighteen years older than when last her saw her, it was softer now. Because of the hair. A face too still for comfort; irises the same color as her skin, which in that still face, used to make … think of mask with mercifully punched-our eyes (Beloved, 9) From the statement above it can be seen that Sethe is an unattractive woman, a woman who has no beauty to be shown. It can be seen also that she has no attention on taking care of her beauty. Her appearance resembles what has happened in her life. She does not even try to cover it; Sethe is kind an open book that offers a whole story just be seeing her performance. Sethe is a rationalist; she realizes her act to kill her daughter is wrong. It shame her-remembering the wonderful soughing trees rather than the boys. Try as she might to make it otherwise, the sycamores beat out the children every time and she could not forgive her memory of that….Her past had been like her present – intolerable- and since she knew death was anything but forgetfulness (Beloved, 6) In addition, she does not want to force the rejection from her society, all the social blaming is something she must receive. Sethe functions as a mother goddess assumed as the one who has the prerogative of choosing life or death for her children. Toward the end of the novel when Sethe is trying to justify her attempts to kill her children, she wants Beloved to understand why, but because Beloved is already gone, Sethe verbalizes it to herself in this way. Another thing that causes Sethe to fight against being like her mother is the mark of slavery. Sethe is a marked daughter of a marked mother. Because of the demand of slave labor, her mother denies physical contact with her. Sethe and her daughter live together. Sethe’s mother’s in law has been died, and her boys running off from the house. She lives in Cincinnati, Ohio, in Northern. The condition shows that Sethe’s are sad after her mother in law has been died. After the mother in law dead, Sethe and her daughter live together. They move to the other city, Cincinnati, Ohio in Northern . Sethe lives alone with her daughter without any relationship with society. She cut off heritage with black women. No more communication likes as usual live in community. From this quotation show that Sethe has an introvert personality. She does not say anything; close her personality and limit of communication. Sethe is a good mother, she loves her children everything, and she take care for her daughter. At the quotation shows that Sethe as a figure of mother and she loves her daughter. Another monologue tells her figure as a good mother. Sethe wants to run away from “Swethome” plantation, she does not care about herself. She saves her children first. Sethe believes that she has been a good mother for their children. As a mother she will do anything. Sethe is a character that has static role as a mother, where sethe only with her son and her work from the beginning of the story until the end of the story. Sethe’s character is consistent with her behaviors: she does not behave one way on one occasion and different way on another unless there is a clear sufficient reason for the change. Sethe is willing to die to protect her daughter, to save from anything that can hurt her daughter “…hard headed daughter Sethe would die to protect (Beloved, 99)” This quotation shows that Sethe is a protected woman, she protect her daughter until she has dead. Sethe sees herself as a mother that loves her children so much, and she will do anything for her children. In her life Sethe makes some relations with other characters especially Denver and Paul D. During their relations they, other characters, also make several opinions about Sethe. They give sufficient comprehension about Sethe’s character. Have close connection to Sethe and support some elaboration about her character Denver believes that her mother is a very affectionate person “The best thing she was, was her children (Beloved, 251)” Sethe does not want Denver hear about her mother’s past, because everything in the past is hurt for Sethe. Paul D sees Sethe as a strong mother it reflected in dialogues and monologues Paul D as a man assumes Sethe loves is too strong to her children, he does not want Sethe to be like that. Because Sethe is not a slave anymore, and she must let her daughter be herself. Every mother dreams of having a happy family. Sethe hopes that her children will have better future than hers. In order to reach the hope, every mother uses their time to be different from another mother, does Sethe. As a child, Sethe realizes that her mother should take care of her children and breastfeed them. However, her realization does not come into existence and she even seldom sees her mother. Noticing, her mother, Sethe also gains a lesson as a mother she should not ignore her duty. She knows that her mother has to work all day instead of taking care of her children. It means that there is no time for her children since her mother has to rest after passing many tiring days. To be a real mother for her children, Sethe is a fighter mother. She struggles to be a true mother for her children. She is a single-parent household. As a mother, Sethe shows that is a woman who not only serves her children but also can help her husband. During her enslavement, Sethe will be trying best to loving al of her children. Unlike her mother, Sethe has protected her children from any violence and brutality especially in slavery condition. Furthermore, she doesn’t have desire to be like her mother since she considers her mother as an irresponsible mother who never loves her children. Sethe’s perspective toward her mother is also her inner conflict which usually happens to a slave mother and her daughter. Furthermore, she also undergoes the same conflict when she becomes a mother herself. Sethe relies on her mother-in-law, Baby Suggs to help her with childcare. Baby Suggs loves and nurtures Sethe’s children as if they were her own. When Baby Suggs is granted her freedom, she takes Howard, Burglar, and Beloved with her in the wagon to cross the river into Ohio. She bargains for a house where she and the children can live until Sethe and Halle, who plan to escape from the Garner plantation, may join them there. Baby Suggs is the sole mother for the children for two months. As a mother, she knows that she is needed by her children. As a result, she manifests her love through a mark which would not be destroyed by anyone. Unlike her mother, she gives her children an understanding about the use of her mark. Besides, the mark is Sethe’s value of motherhood for all her children if one day her children have to re-identify her mother. Although they have the same aim of marking themselves, still Sethe’s aim is deeper than that of her mother. She does not only show that she is her children’s mother but also demonstrates it through her duty as a responsible mother. Sethe was a slave daughter. To be a slave daughter, she is conscious of being ignored by her mother. As a result, she has hoped for something different for her children and she intends to make a revolution which could change the relationship between her and her daughter. She hopes for a future with less stress and more joy for her children. Of course, every mother has a great hope for her children whatever the condition is. Sethe is threatened by the danger from slavery but it doesn’t seem to cause her desperation. For the second time, she faces the trouble when she was on her journey to Ohio. However, this problem makes her to have stronger hope than before. Sethe attempts to run away and disguises herself because she is recaptured. One reason of her deception on the surface is just to hide her identity. However, another reason is that her responsibility toward her daughter. She is aware that hey daughter depends on her and the capture causes her daughter to lose her hope. In other words, she is a persevering mother who sacrifices herself for the sake of her daughter. Teaching her daughter to be independent is one of Sethe’s aims as a mother. She teaches her daughter not to be dependent on another person when she still can help herself. Seethe gives the lesson to Denver, when she was deserted by Paul D. Although Paul D leaves Sethe because of her ‘brutal’ deed, she did not plead with him not to leave her alone after knowing it. As a result, it can be assumed that Sethe is an independent mother who never comes under the subordination of masculine authority in this case Paul D. Her self-reliance influences her to be a preserving mother in facing all the condition. However, her effort of teaching her daughter to be independent is not accepted by Denver easily. Denver just thinks that her mother wants to cover her past fault which cannot be forgiven by anyone including her and Paul D. On the contrary, she even blames her mother and thinks that her mother ought to be left her lover. This misunderstanding brings about Sethe’s inner conflict as a mother. Actually, she has a desire to teach her daughter to be independent but she cannot be independent. She still needs the help from Paul D. She begins to think that she is a useless mother who fails to protect her daughter who died. Doing simple work such as housework is one of Sethe’s efforts to attain her daughter’s love. She believes that this effort would create her daughter’s love toward her. Because of the reason, Sethe prepares breakfast for Denver before she goes to work. Certainly, working is one of her duties as a mother of single-parent household because of the absence of the father. Another case with Denver, he has even a thought that her mother has turned her love to other people. As a result, the coming of Paul D causes Sethe’s inner conflict. Sethe actually loves Denver but she also has love for Paul D. Sethe loves both of them and Denver’s suspicion makes her inner conflict come to surface. She feels that she fails in playing role as a mother. The authority of an African-American mother is also questioned by her adolescent daughter. Furthermore, the mother cannot avoid being criticized by her daughter. Sethe also undergoes the problem when Denver asks about her marriage. At this time, Denver enters a period of mistrust toward her mother by asking continuously where her diamonds are. Denver thinks that Sethe’s diamonds are the remembrance of her father and as a value of loyalty toward her father. Because of that, Denver does not stop asking the diamonds when Paul D comes to that house for the very first day. In fact at the same time, Denver intends to know how far Sethe’s authority of deciding something in this case not to wear the diamonds. Again, Sethe’s inner conflict arises but this conflict can be overcomed. She overcomes the conflict by applying the fature as a mother of a single-parent household who has an authority to control over her daughter’s live. Since then, Denver can do nothing toward what her mother has decided. Sethe does not only concern about her daughter’s physical needs but also her spiritual needs. She tries to communicate with her daughter whenever she has time. Although her past experiences was an unpleasant one, she tells Denver in such a way that Denver is pleased with it. By doing this, Denver gets a kind of satisfaction from her mother story about her. Denver loves the story of her birth from whom she was helped by a white lady. She also gets her name from that lady. As a result, it is understandable why Denver feels proud of her mother’s story about her. At the same time, Sethe accomplishes her goal of fulfilling Denver’s spiritual needs although she has to suffer from the burdens. THE INFLUENCE OF SLAVERY TO SETHE’S MOTHERHOOD Slavery is terrible for men; but it is far more terrible for women. Superadded for the burden common to all, they have wrongs, sufferings, and mortifications peculiarly their own (Kerber & De Hart, 1991: 105). The images of African-American women that grew out of the slavery era relect the fact that black males and females do not experinces slavery in the same way. According to Ruiz and Dubois, in plantation, slave women have a function within two communities: one structures by white masters, the other by slave themselves. The key to woman’s role in both is work. In the former labor is imposed upon blacks as their principle obligation; in the later, labor is a primary concern by necessity. In both arenas, women’s work embrance the production of goods and services and the production of human beings (Ruiz & Dubois, 1994: 4) Sethe has to endure double burdens, which are of sexism (in a gender and sexuality harassment) and racism (the act of resisting race). With fortitude, she has to accept the condition of slavery that does not permit her to be together with her husband and her own children. In the other words, the generation of Sethe’s family is almost the same with what she experinced. Fortunately, she still has a chance to raise her children although the way is not proper. At first it is her husband who makes decison for the family especially when they want to run way. Nevertheless, Sethe should be responsible for her four children. When she realizes the changing function in her family, Sethe does all the things awkwardly In Toni Morrison’s Beloved, Sethe’s traumatic experiences. Her traumatic backgrounds are revealed through some following evidences when she lived in plantation system in the Southern. Morrison also creates a link between public and personal memories through the character of Beloved. Sethe says to Denver, “Some things go. Pass on. Some things just stay. I used to think it was my rememorize. You know. Some things you forget. Other things you never do. But it’s not . . . even if I die, the picture of what I did, or knew, or saw is still out there, living, breathing, eating”. (Beloved, 36). Sethe give advice for Denver. Denver loves her mother, because Sethe is a patient mother. This fact make Denver never leaves her mother although the black society surrounding her rejects her family. Sethe does not want Denver hear about her mother’s past, because everything in the past is hurt for Sethe. For Denver, Beloved “held for her all the anger, love and fear she didn’t know what to do with” (Beloved, 103). Interpreted about Beloved. Sethe angers with all of attitude. They confront not only Sethe’s past but their own past as well: “when they caught up with each other, all thirty, and arrived at 124, the first thing they saw was not Denver sitting on the steps, but themselves. Younger, stronger, even as little girls lying in the grass a sleep” (Beloved, 258). The confrontation of Sethe not only at the own past but also own past as well. Actually, as an intellectual master, schoolteacher should not allow the immoral behavior to his tudents. Because of that reason, Sethe who is a slave is not only inferior in the sense of her status but also case of her sex. The novel cen